Realization of high mobility p-type co-doped ZnO: AlN film with a high density of nitrogen-radicals - Lee, J; Lee, J; Cha, S; Kim, J; Seo, D; Bin Im, W; Hong, J (2009)
High mobility p-type ZnO:AlN thin films have been efficiently realized by utilizing pre-activated nitrogen (N) plasma sources with an inductively coupled dual target co-sputtering system. High density of N-plasma-radicals was generated with an additional RF power applied through a ring-shaped quartz-tube located inside the chamber during co-sputtering process. The AlN codoped ZnO film shows excellent p-type behavior with a high mobility and a hole concentration of 154 cm2°V- 1s- 1 and about 3 × 1018°cm- 3 at 600 °C, respectively. Electrical properties of p-n homo-junction devices based on p-type ZnO film are also discussed. © 2009 Elsevier B.V.